Association between an increase in serum sodium and in-hospital mortality in critically ill patients - Grim, CCA; Termorshuizen, F; Bosman, RJ; Cremer, OL; Meinders, AJ; Nijsten, MWN; Pickkers, P; de Man, AME; Schultz, MJ; van Vliet, P; Weigel, JD; Helmerhorst, HJF; et al. (Lippincott, Williams and Wilkins, 2021)
OBJECTIVES: In critically ill patients, dysnatremia is common, and in these patients, in-hospital mortality is higher. It remains unknown whether changes of serum sodium after ICU admission affect mortality, especially whether normalization of mild hyponatremia improves survival.